Reactions of laser-ablated aluminum atoms with nitrogen during condensation at 10 K. Infrared spectra and density functional calculations for Alx Ny molecular: Low-Temperature Physics and Chemistry in Cryomatrice - Andrews, Lester; Zhou, Mingfei; Chertihin, George V.; Bare, William D.; Hannachi, Yacine (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Laser-ablated aluminum atoms react with dinitrogen on condensation at 10 K to form N3 radical andthe subject molecules, which are identified by nitrogen isotopic substitution, further reactions onannealing, and comparison with isotopic frequencies computed by density functional theory. The major AlN3 product is identified from three fundamentals and a statistically mixed nitrogen isotopic octetpattern. The aluminum rich Al2N and Al3N species are major products on annealing to allow diffusion and further reaction of trapped species. This work provides the first experimental evidence for molecularAlxNy species that may be involved in ceramic film growth.